2018
DOI: 10.1259/dmfr.20180068
|View full text |Cite
|
Sign up to set email alerts
|

Does acoustic radiation force elastography improve the diagnostic capability of ultrasound in the preoperative characterization of masses of the parotid gland?

Abstract: VTQ in combination with classical ultrasound examination provides additional data useful in distinguishing between benign and malignant tumours and thus shows promise for integration into preexisting ultrasound protocols. However, despite the improvement, clear differentiation of tumours is still not possible and further investigation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Regardless of the reason, we were consistently unsuccessful both in differentiating various tumor entities from one another and in distinguishing benign from malignant masses using both US devices (Table 4). These findings support and in particular augment previous results (24,29,35,(38)(39)(40), while opposing others (25,34,41,42).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Regardless of the reason, we were consistently unsuccessful both in differentiating various tumor entities from one another and in distinguishing benign from malignant masses using both US devices (Table 4). These findings support and in particular augment previous results (24,29,35,(38)(39)(40), while opposing others (25,34,41,42).…”
Section: Discussionsupporting
confidence: 90%
“…The use and benefits of strain elastography and different shear wave elastography techniques in PG lesions have been assessed before, but statements diverged greatly as to whether sonoelastography in general can be considered helpful in identifying PG lesions (15,(24)(25)(26)(27)(28)(29). A former meta-analysis concluded that quantitative methods-as the ARFI-technique we used in this study-have provided more stable results than semi-quantitative methods (30).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…VTIQ includes several share wave modes such as: velocity, quality, travel time, and displacement. VTIQ in combination with routine US techniques provides additional data useful in distinguishing benign from malignant parotid tumors [41,42].…”
Section: Ultrasound Elastographymentioning
confidence: 99%